Intuição e interioridade em Bergson - Pellegrino, Rafael (2022)
The present work investigates the meaning of the notion of interiority in Henri Bergson’s philosophy and its role in the Bergsonian conception of intuition. It starts with the following thought: either the intuition of an “exteriority” is a nonsense, or the way in which Bergson brings together the notions of interiority and duration, through his notion of intuition, should lead us to a resignification of the very meaning of what we could call interiority. But then the very idea of exteriority will undergo a resignification within the philosopher's doctrine. It should be noted that this work is not intended to exhaust all the problems that can be raised in this regard. Rather, this thesis is limited to raising some points in which the notion of intuition seems to suggest a very unique way of thinking about what interiority means in the work of Henri Bergson.